Carbonyl iron powder composite material and preparation method thereof

Through the secondary insulating treatment and spray drying process of amorphous cobalt-based materials and carbonyl iron powder, combined with the use of surfactants, the oxidation problem of carbonyl iron powder under high frequency conditions is solved, and its permeability and stability are improved. , achieving low loss and high magnetic induction strength.

CN117476351BActive Publication Date: 2024-12-20HUACUI MICROMAG ELECTRONICS (JIANGSU) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311470307.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-07
Publication Date
2024-12-20
Estimated Expiration
2043-11-07

AI Technical Summary

Technical Problem

Carbonyl iron powder is easily oxidized under high-frequency conditions, resulting in a decrease in magnetic properties and large eddy current loss. After modification of the prior art, the magnetic permeability is low and the resistivity is unstable, the preparation process is complicated, and impurity problems are prone to occur.

Method used

The amorphous cobalt-based material and carbonyl iron powder were subjected to secondary insulation treatment, mixed uniformly and spray-dried under the protection of inert gas, and surfactant was added to improve insulation pressure resistance and magnetic permeability.

Benefits of technology

It improves the stability and magnetic permeability of carbonyl iron powder composite material, reduces eddy current loss, enhances magnetic induction strength and resistivity, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117476351B_ABST
    Figure CN117476351B_ABST
Patent Text Reader

Abstract

The present invention provides a carbonyl iron powder composite material and a preparation method thereof. The preparation method of the carbonyl iron powder composite material comprises the following steps: performing secondary insulation treatment on an amorphous cobalt-based material; performing secondary insulation treatment on carbonyl iron powder; uniformly mixing the amorphous cobalt-based material after the secondary insulation treatment and the carbonyl iron powder, and mixing them under the protection of an inert gas to form a mixed solution; passing the mixed solution through a spray drying device to spray it into tiny droplets, and rapidly drying it at 160 to 220° C. to obtain a carbonyl iron powder composite material. Compared with the prior art, the carbonyl iron powder composite material prepared by the present invention has better insulation withstand voltage performance, while improving stability, reducing eddy current loss, improving magnetic permeability and saturation magnetic flux density, and improving magnetic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic material preparation, and in particular to a carbonyl iron powder composite material and a preparation method thereof. Background Art

[0002] Carbonyl iron powder has a special onion-shaped structure and high saturation magnetic induction intensity and magnetic permeability, so it is widely used in mobile communications, intelligent manufacturing, automotive electronics, and new energy electronics. However, carbonyl iron powder has low resistivity and poor stability. It is very easy to oxidize above 170°C, resulting in large eddy current losses in carbonyl iron powder under high-frequency conditions and a serious decrease in magnetic properties.

[0003] In order to improve the stability and magnetic properties of carbonyl iron powder and reduce its eddy loss, the surface of carbonyl iron powder is generally improved. Amorphous materials have been the focus of scientific and industrial circles since their discovery due to their special organizational structure, efficient preparation process and excellent material properties. There are also methods in the prior art to modify carbonyl iron powder by amorphous materials, but since the magnetic permeability of carbonyl iron itself is low, the magnetic permeability of the composite material obtained after adding amorphous materials is also low, which may not meet some application scenarios with high magnetic permeability requirements. In addition, it is easy to have problems such as unstable resistivity, complicated preparation process, and easy to have impurities.

[0004] In view of this, it is indeed necessary to provide a carbonyl iron powder composite material and a preparation method thereof to solve the above problems. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a carbonyl iron powder composite material, which has strong stability, low eddy current loss and high magnetic permeability.

[0006] To achieve the above object, the present invention provides a method for preparing a carbonyl iron powder composite material, comprising the following steps:

[0007] Perform secondary insulation treatment on amorphous cobalt-based materials;

[0008] Perform secondary insulation treatment on carbonyl iron powder;

[0009] The amorphous cobalt-based material after secondary insulation treatment and the carbonyl iron powder are uniformly mixed and mixed under the protection of an inert gas to form a mixed solution;

[0010] After the mixed solution is atomized into droplets in a drying chamber of a spray drying device, water is rapidly vaporized in contact with hot air and dried at 160-220° C. to form a carbonyl iron powder composite material.

[0011] As a further improvement of the present invention, the mass ratio of the amorphous cobalt-based material to the carbonyl iron powder is 1:1-1:3.

[0012] As a further improvement of the present invention, the amorphous cobalt-based material is Co a Fe b B c Si d C e , where a+b≥1 / 2(a+b+c+d+e).

[0013] As a further improvement of the present invention, the Co a Fe b B c Si d C e Among them, the content of Co is 30~50wt%; the content of Fe is 20~40wt%; the content of B is 5~20wt%; the content of Si is 5~20wt%; and the content of C is 1~10wt%.

[0014] As a further improvement of the present invention, before the mixed solution is spray-dried, a surfactant is added to the mixed solution, and stirring is continued under the protection of an inert gas to obtain a stable mixed solution.

[0015] As a further improvement of the present invention, the surfactant is at least one of polyvinyl alcohol, gelatin or a silane coupling agent.

[0016] As a further improvement of the present invention, the amorphous cobalt-based material is first insulated by an inorganic insulating agent, and then the amorphous cobalt-based material is insulated for a second time by an organic insulating agent, wherein the inorganic insulating agent is tetraethyl orthosilicate, and the organic insulating agent is an epoxy resin mixture.

[0017] As a further improvement of the present invention, the carbonyl iron is first insulated with an inorganic insulating agent, and then the carbonyl iron is insulated again with an organic insulating agent, wherein the inorganic insulating agent is phosphoric acid or a mixture thereof, and the organic insulating agent is an epoxy resin mixture and a silane coupling agent.

[0018] As a further improvement of the present invention, the epoxy resin mixture includes epoxy resin A and epoxy resin B, wherein the ratio of epoxy resin A to epoxy resin B is 3:1~6:1.

[0019] The present invention further provides a carbonyl iron powder composite material, which is prepared by the above-mentioned method for preparing the carbonyl iron powder composite material.

[0020] The beneficial effects of the present invention are as follows: compared with the prior art, the carbonyl iron powder composite material and the preparation method thereof of the present invention improve the insulation withstand voltage performance and resistivity of the amorphous cobalt-based material and the carbonyl iron powder through secondary insulation treatment, and at the same time, the amorphous cobalt-based material and the carbonyl iron powder that have undergone secondary insulation treatment are mixed to prepare the carbonyl iron powder composite material, so as to improve the magnetic permeability of the carbonyl iron powder composite material, and the composite material has high saturation magnetic induction intensity and low loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a scanning electron microscope image of the soft magnetic composite material of the present invention.

[0022] Figure 2 It is a preparation flow chart of the soft magnetic composite material of the present invention. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0024] It should be noted here that in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the accompanying drawings, while other details that are not closely related to the present invention are omitted.

[0025] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0026] See also Figure 1 As shown, the present invention provides a method for preparing a carbonyl iron powder composite material, comprising the following steps:

[0027] S1: Perform secondary insulation treatment on amorphous cobalt-based materials;

[0028] S2: Perform secondary insulation treatment on the carbonyl iron powder;

[0029] S3: uniformly mixing the amorphous cobalt-based material after secondary insulation treatment and the carbonyl iron powder, and mixing them under the protection of an inert gas to form a mixed solution;

[0030] S4: After the mixed solution is atomized into droplets in the drying chamber of a spray drying device, the water is rapidly vaporized in contact with hot air and dried at 160-220°C to form a carbonyl iron powder composite material. The spray drying process conditions are: a feed flow rate of 0.2-10 L / min, an inlet temperature of 120-160°C, and an outlet temperature of 70-80°C.

[0031] The amorphous cobalt-based material and carbonyl iron powder are subjected to secondary insulation treatment to improve their insulation withstand voltage performance and resistivity. At the same time, the amorphous cobalt-based material and carbonyl iron powder subjected to secondary insulation treatment are mixed to prepare a carbonyl iron powder composite material to improve the magnetic permeability of the carbonyl iron powder composite material, which has high saturation magnetic induction intensity and low loss.

[0032] Furthermore, the mass ratio of the amorphous cobalt-based material to the carbonyl iron powder is 1:1-1:3.

[0033] Preferably, the amorphous cobalt-based material is Co a Fe b B c Si d C e , where a+b≥1 / 2(a+b+c+d+e), the Co a Fe b B c Si d C e Among them, the content of Co is 30~50wt%; the content of Fe is 20~40wt%; the content of B is 5~20wt%; the content of Si is 5~20wt%; and the content of C is 1~10wt%.

[0034] Furthermore, before the mixed solution is spray-dried, a surfactant is added to the mixed solution, and stirring is continued under the protection of an inert gas to obtain a stable mixed solution.

[0035] Furthermore, the surfactant is at least one of polyvinyl alcohol, gelatin or a silane coupling agent.

[0036] Furthermore, the amorphous cobalt-based material is firstly insulated by an inorganic insulating agent, and then the amorphous cobalt-based material is secondarily insulated by an organic insulating agent, wherein the inorganic insulating agent is tetraethyl orthosilicate, and the organic insulating agent is an epoxy resin mixture.

[0037] Furthermore, the carbonyl iron is first insulated with an inorganic insulating agent, and then the carbonyl iron is insulated again with an organic insulating agent, wherein the inorganic insulating agent is phosphoric acid or a mixture thereof, and the organic insulating agent is an epoxy resin mixture and a silane coupling agent.

[0038] Furthermore, the epoxy resin mixture includes epoxy resin A and epoxy resin B, wherein the ratio of epoxy resin A to epoxy resin B is 3:1-6:1.

[0039] The present invention further provides a carbonyl iron powder composite material, which is prepared by the above-mentioned method for preparing the carbonyl iron powder composite material.

[0040] The following is a detailed description through specific embodiments.

[0041] Embodiment 1:

[0042] Secondary insulation treatment of amorphous cobalt-based materials.

[0043] The amorphous cobalt-based material is first insulated with an inorganic insulating agent, and then the amorphous cobalt-based material is insulated for a second time with an organic insulating agent, wherein the inorganic insulating agent is tetraethyl orthosilicate, and the organic insulating agent is epoxy resin A and epoxy resin B, wherein the ratio of epoxy resin A to epoxy resin B is 5:1.

[0044] Preferably, the amorphous cobalt-based material is Co 25 Fe 40 B 15 Si 16 C4.

[0045] First, dissolve ethyl orthosilicate in a mixed solution of anhydrous ethanol and water, then add Co 25 Fe 40 B 15 Si 16 C4, after stirring evenly, add ammonia water dropwise, heat and stir at 80°C until the solution is completely volatilized, and then bake at 100°C for 1 hour until the powder is completely dry. Then, epoxy resin A and epoxy resin B are dissolved in acetone solution, and the dry cobalt-based amorphous powder insulated with ethyl orthosilicate is poured into the acetone solution containing the epoxy resin mixture, and stirred at 60°C until the acetone is completely volatilized, that is, the cobalt-based amorphous powder after secondary insulation is obtained.

[0046] The carbonyl iron powder is subjected to secondary insulation treatment.

[0047] The carbonyl iron is first insulated with an inorganic insulating agent, and then the carbonyl iron is insulated again with an organic insulating agent, wherein the inorganic insulating agent is phosphoric acid, and the organic insulating agent is a mixture of epoxy resins and a silane coupling agent. The organic insulating agent is epoxy resin A and epoxy resin B, wherein the ratio of epoxy resin A to epoxy resin B is 5:1, and the silane coupling agent is KH550.

[0048] First, phosphoric acid is dissolved in acetone solution and dispersed, then carbonyl iron powder is poured in, heated and stirred at 60°C until acetone is completely volatilized, and dry carbonyl iron powder after phosphoric acid insulation is obtained. Then epoxy resin A and epoxy resin B (ratio of 5:1) and silane coupling agent KH550 are dissolved in acetone solution, and then the dry carbonyl iron powder after phosphoric acid insulation is poured into the acetone solution containing epoxy resin mixture and silane coupling agent, and stirred at 60°C until acetone is completely volatilized, that is, carbonyl iron powder after secondary insulation is obtained.

[0049] The amorphous cobalt-based material after secondary insulation treatment and the carbonyl iron powder are evenly mixed in a ratio of 1:2, and mixed under the protection of nitrogen to form a mixed solution.

[0050] Furthermore, under the protection of nitrogen, polyvinyl alcohol was added to the mixed solution to improve the dispersion effect, and the mixture was fully mixed under the action of a strong magnetic field to make Co 25 Fe 40 B 15 Si 16 C4 is adsorbed on the surface of carbonyl iron powder.

[0051] Under nitrogen protection, the mixture was stirred at room temperature for 12 hours to form a homogeneous mixed solution.

[0052] After the mixed solution is atomized into droplets in the drying chamber of the spray drying device, the water vaporizes rapidly in contact with hot air and is dried at 160-220°C to form a carbonyl iron powder composite material. The spray drying process conditions are: feed flow rate of 0.2-10L / min, inlet temperature of 120-160°C, and outlet temperature of 70-80°C.

[0053] See also Figure 2 The following is a scanning electron microscope image of the carbonyl iron powder composite material. Figure 2 It can be seen that the carbonyl iron powder composite material has high sphericity and uniform particle size, ranging from 1 to 5 μm.

[0054] The prepared carbonyl iron powder composite material was subjected to performance testing together with Comparative Example 1 (wherein, Comparative Example 1 is unmodified carbonyl iron powder) and Comparative Example 2 (Comparative Example 2 is carbonyl iron powder subjected to secondary insulation according to the above method). The saturation magnetic induction intensity of the three was measured by magnetic measurement, and the resistivity was measured by a four-probe method. The corrosion potential and corrosion current of the three were measured by electrochemical measurement. The results are shown in Table 1.

[0055] Table 1 Performance comparison of Comparative Example 1, Comparative Example 2 and Example 1

[0056]

[0057] It can be seen from Table 1 that the carbonyl iron powder composite material of Example 1 has the best performance, and its magnetic saturation induction intensity and resistivity are higher than those of the carbonyl iron powder (Comparative Example 2) treated with secondary insulation and the carbonyl iron powder (Comparative Example 1) without any modification, and its corrosion potential and corrosion current are lower than those of Comparative Example 2 and Comparative Example 1. This is because the amorphous cobalt-based material has a strong magnetic property. By adding an appropriate amount of amorphous cobalt-based material to the carbonyl iron powder, the overall magnetic properties of the carbonyl iron powder composite material can be enhanced, and its magnetic saturation intensity and saturation magnetic induction intensity can be improved. Moreover, the addition of amorphous cobalt-based material treated with insulation can improve the conductive properties of the carbonyl iron powder and promote the flow of current in the carbonyl iron powder composite material. In addition, the amorphous cobalt-based material is attached to the surface of the carbonyl iron powder, which can also have a certain protective effect on the carbonyl iron powder and improve the stability and durability of the carbonyl iron powder composite material.

[0058] Embodiment 2:

[0059] Secondary insulation treatment of amorphous cobalt-based materials.

[0060] The amorphous cobalt-based material is first insulated with an inorganic insulating agent, and then the amorphous cobalt-based material is insulated for a second time with an organic insulating agent, wherein the inorganic insulating agent is tetraethyl orthosilicate, and the organic insulating agent is epoxy resin A and epoxy resin B, wherein the ratio of epoxy resin A to epoxy resin B is 4:1.

[0061] Preferably, the amorphous cobalt-based material is Co 65 Fe8B 19.5 Si 4.5 C3.

[0062] First, dissolve ethyl orthosilicate in a mixed solution of anhydrous ethanol and water, then add Co 65 Fe8B 19.5 Si 4.5 C3, after stirring evenly, add ammonia water dropwise, heat and stir at 80°C until the solution is completely volatilized, and then bake at 100°C for 1 hour until the powder is completely dry. Then, epoxy resin A and epoxy resin B are dissolved in acetone solution, and the dry cobalt-based amorphous powder insulated with ethyl orthosilicate is poured into the acetone solution containing the epoxy resin mixture, and stirred at 60°C until the acetone is completely volatilized, that is, the cobalt-based amorphous powder after secondary insulation is obtained.

[0063] The carbonyl iron powder is subjected to secondary insulation treatment.

[0064] The carbonyl iron is first insulated with an inorganic insulating agent, and then the carbonyl iron is insulated again with an organic insulating agent, wherein the inorganic insulating agent is a mixture of phosphoric acid and nitric acid, wherein the ratio of phosphoric acid to nitric acid is 25:1, and the organic insulating agent is an epoxy resin mixture and a silane coupling agent. The organic insulating agent is epoxy resin A and epoxy resin B, wherein the ratio of epoxy resin A to epoxy resin B is 4:1, and the silane coupling agent is KH550.

[0065] First, phosphoric acid is dissolved in acetone solution and dispersed, then carbonyl iron powder is poured in, heated and stirred at 60°C until acetone is completely volatilized, and dry carbonyl iron powder after phosphoric acid insulation is obtained. Then epoxy resin A and epoxy resin B (ratio is 4:1) and silane coupling agent KH550 are dissolved in acetone solution, and then the dry carbonyl iron powder after phosphoric acid insulation is poured into the acetone solution containing epoxy resin mixture and silane coupling agent, and stirred at 60°C until acetone is completely volatilized, that is, carbonyl iron powder after secondary insulation is obtained.

[0066] The amorphous cobalt-based material after secondary insulation treatment and the carbonyl iron powder are evenly mixed in a ratio of 1:3, and mixed under the protection of nitrogen to form a mixed solution.

[0067] Furthermore, under the protection of nitrogen, gelatin was added to the mixed solution to improve the dispersion effect, and the mixture was fully mixed under the action of a strong magnetic field to make Co 65 Fe8B 19.5 Si 4.5 C3 is adsorbed on the surface of carbonyl iron powder.

[0068] Under nitrogen protection, the mixture was stirred at room temperature for 16 hours to form a homogeneous mixed solution.

[0069] After the mixed solution is atomized into droplets in the drying chamber of the spray drying device, the water vaporizes rapidly in contact with hot air and is dried at 160-220°C to form a carbonyl iron powder composite material. The spray drying process conditions are: a feed flow rate of 0.2-10L / min, an inlet temperature of 120-160°C, and an outlet temperature of 70-80°C. The carbonyl iron powder composite material has high sphericity and a uniform particle size of 1-5μm.

[0070] The magnetic induction intensity was measured by magnetic measurement, the resistivity was measured by four-probe method, and the corrosion potential and corrosion current of the three were measured by electrochemical method. The results are shown in Table 2.

[0071] Table 2 Performance test results of Example 2

[0072]

[0073] It can be seen from Table 2 that the carbonyl iron powder composite material of Example 2 has the best performance, and its magnetic saturation induction intensity and resistivity are higher than those of the carbonyl iron powder composite material of Example 1, and higher than the carbonyl iron powder subjected to secondary insulation treatment (Comparative Example 2) and the carbonyl iron powder without any modification (Comparative Example 1), and its corrosion potential and corrosion current are lower than those of Comparative Example 2 and Comparative Example 1. This is because the content of amorphous cobalt-based material in Example 2 is higher than that in Example 1, and the amorphous cobalt-based material has strong magnetism, which can enhance the overall magnetic properties of the carbonyl iron powder composite material and improve its magnetic saturation intensity and saturation magnetic induction intensity.

[0074] In summary, the carbonyl iron powder composite material and the preparation method thereof of the present invention perform secondary insulation treatment on the amorphous cobalt-based material and the carbonyl iron powder to improve their insulation withstand voltage performance and resistivity, and at the same time, the secondary insulation treated amorphous cobalt-based material and the carbonyl iron powder are mixed to prepare the carbonyl iron powder composite material to improve the magnetic permeability of the carbonyl iron powder composite material, and have high saturation magnetic induction intensity and low loss.

[0075] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a carbonyl iron powder composite material, It is characterized in that The following steps are involved: Performing secondary insulation treatment on the amorphous cobalt-based material, firstly performing insulation treatment on the amorphous cobalt-based material with an inorganic insulating agent, and then performing secondary insulation treatment on the amorphous cobalt-based material with an organic insulating agent, wherein the inorganic insulating agent is tetraethyl orthosilicate, and the organic insulating agent is an epoxy resin mixture; Performing secondary insulation treatment on the carbonyl iron powder, firstly performing insulation treatment on the carbonyl iron with an inorganic insulating agent, and then performing secondary insulation treatment on the carbonyl iron with an organic insulating agent, wherein the inorganic insulating agent is phosphoric acid or a mixture thereof, and the organic insulating agent is an epoxy resin mixture and a silane coupling agent; The amorphous cobalt-based material after secondary insulation treatment and the carbonyl iron powder are uniformly mixed and mixed under the protection of an inert gas to form a mixed solution; The mixed solution is sprayed into tiny droplets by a spray drying device, and rapidly dried at 160-220° C. to obtain a carbonyl iron powder composite material; The mass ratio of the amorphous cobalt-based material to the carbonyl iron powder is 1:1 to 1:3; the amorphous cobalt-based material is Co a Fe b B c Si d C e , wherein a+b≥1 / 2(a+b+c+d+e); the Co a Fe b B c Si d C e The content of Co is 30-65wt%; the content of Fe is 8-20wt%, and the content of Co is greater than that of Fe; the content of B is 5-20wt%; the content of Si is 5-20wt%; and the content of C is 1-10wt%.

2. The method for preparing the carbonyl iron powder composite material according to claim 1, It is characterized in that Also includes: Before spray drying the mixed solution, a surfactant is added to the mixed solution, and stirring is continued under the protection of an inert gas to obtain a stable mixed solution.

3. The method for preparing the carbonyl iron powder composite material according to claim 2, It is characterized in that The surfactant is at least one of polyvinyl alcohol, gelatin or a silane coupling agent.

4. The method for preparing the carbonyl iron powder composite material according to claim 1, It is characterized in that The epoxy resin mixture comprises epoxy resin A and epoxy resin B, wherein the ratio of epoxy resin A to epoxy resin B is 3:1 to 6:

1.

5. A carbonyl iron powder composite material, It is characterized in that The carbonyl iron powder composite material is prepared by the preparation method of any one of claims 1 to 4.

Citation Information

Patent Citations

  • Manufacturing method of high-superposition low-loss metal magnetic powder core

    CN103594218A

  • Magnetic powder for manufacturing magnet, magnet and magnetic element

    CN116670314A

  • Dust core and manufacturing method thereof

    JP2010258309A

  • Dust core, method for producing said dust core, inductor provided with said dust core, and electronic / electrical device on which said inductor is mounted

    WO2018207521A1